2011
DOI: 10.1111/j.1600-0714.2011.01058.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary intraosseous squamous cell carcinoma arising in an odontogenic cyst - a clinicopathologic analysis of 116 reported cases

Abstract: J Oral Pathol Med (2011) 40: 733–738 Purpose:  To review the literature on primary intraosseous squamous cell carcinoma (PIOSCC) associated with odontogenic cyst. Methods:  All well‐documented cases of PIOSCC published between 1938 and 2010 were collected. Only cases of PIOSCC arising from the lining of an odontogenic cyst, including the keratocystic odontogenic tumor, were selected. Age, sex, signs and symptoms, affected jaw, cyst type, treatment, histopathology, and outcome were recorded. Results:  The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
166
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(177 citation statements)
references
References 91 publications
(109 reference statements)
6
166
2
3
Order By: Relevance
“…The 2-year survival rate was 83.3% (10/12). Chantravekin et al (39) reported that the 2-year survival rate was 60.0%, while Bodner et al (13) reported that the 2-and 5-year survival rates were 62 and 38%, respectively. There were significant differences in survival rate between the present study and previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 2-year survival rate was 83.3% (10/12). Chantravekin et al (39) reported that the 2-year survival rate was 60.0%, while Bodner et al (13) reported that the 2-and 5-year survival rates were 62 and 38%, respectively. There were significant differences in survival rate between the present study and previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Bodner et al (13) analyzed 116 reported cases of PIOSCC arising in an odontogenic cyst and found that the majority of the cases exhibited mandibular involvement, whereas the maxilla was affected in 21% of the cases. For the present report, we searched for cases of PIOSCC derived from a maxillary odontogenic cyst.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it may be diffi cult to diff erentiate between keratocystic odontogenic tumours and radicular cysts before surgery. Even if the lesion is diagnosed preoperatively as a radicular cyst, we recommend complete removal -particularly because malignant transformation has been reported (5,(13)(14)(15) .…”
Section: Confl Icts Of Interestmentioning
confidence: 99%
“…According to Browne et.al 1 the sex predilection of dentigerous cyst is 1.6:1(male: female). Sometimes, lining of dentigerous cysts may transform into malignancies like squamous cell carcinoma(SCC) 2,3,4,5,6 (50%), mucoepidermoid carcinoma(MEC) 7,8 (50%), ameloblastoma 9 (14.6%) and adenomatoid odontogenic tumour(AOT) 10 (73%).…”
Section: Introduction:-mentioning
confidence: 99%